(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article presents reflections on the development of professional qualities in future teachers and draws relevant conclusions. Methodical recommendations are provided regarding the pedagogical skills and professional competence of teachers when working with students who have gaps in their knowledge, skills, and competencies. The article highlights the importance of pedagogical mastery in a teacher’s professional activity, the ability to generalize experience, and the role of the teacher as a personality in the process of educating students. Аннотация: В данной статье рассмотрены вопросы формирования профессиональных качеств у будущих учителей и сделаны соответствующие выводы. Приведены методические рекомендации по педагогическому мастерству и профессиональной компетентности учителя при работе с учащимися, имеющими пробелы в знаниях, умениях и навыках. Рассмотрено значение педагогического мастерства в деятельности учителя, обобщение педагогического опыта, а также формирование личности учителя в процессе передачи знаний учащимся.